PD-L1 expression predicts the efficacy of PD-1 blockade plus chemotherapy versus chemotherapy alone in treatment-naïve advanced or metastatic gastric cancer: a pooled analysis of reconstructed individual patient-level data from two randomized trials - Zhou, Wei; Cai, Zeng-Zhi; Fan, Zhuolin; Zheng, Xu; Chen, Yu-Tong (Frontiers in Cell and Developmental Biology, 2025)
BackgroundChemotherapy alone exhibits suboptimal efficacy in patients with treatment-naïve advanced gastric cancer (GC). Randomized controlled trials (RCTs) have demonstrated that combining Programmed Cell Death Protein-1 (PD-1) blockade with chemotherapy significantly improves overall survival (OS) compared to chemotherapy alone. However, the efficacy of PD-1 inhibitors in patients with low Programmed Cell Death-Ligand 1 (PD-L1) expression remains unclear.MethodsElectronic databases were searched for RCTs comparing PD-1/PD-L1 inhibitors plus chemotherapy to placebo plus chemotherapy or chemotherapy alone in treatment-naïve advanced gastric or gastroesophageal junction adenocarcinoma patients. Individual patient-level data (IPD) for overall survival (OS) and progression-free survival (PFS) were reconstructed. The KMSubtraction algorithm was employed to derive IPD for the PD-L1-low subgroup. Treatment effects in PD-L1-high and PD-L1-low subgroups were evaluated using Cox proportional hazards models with shared frailty to account for between-study heterogeneity. Interaction tests were performed to assess differences in treatment effects between these subgroups.ResultsNine RCTs were included in the qualitative analysis. A combined positive score (CPS) of 5 was selected as the cutoff for analysis, with CheckMate 649 and ORIENT-16 trials included. In the CPS<5 subgroup, OS (CheckMate 649: HR = 0.97, 95% CI 0.81–1.17, P = 0.758; ORIENT-16: HR = 0.94, 95% CI 0.68–1.31, P = 0.725) and PFS (CheckMate 649: HR = 0.95, 95% CI 0.79–1.14, P = 0.580; ORIENT-16: HR = 0.73, 95% CI 0.52–1.01, P = 0.055) did not significantly differ between patients receiving PD-1 blockade plus chemotherapy and those receiving chemotherapy alone. Pooled analysis of reconstructed OS IPD from CheckMate 649 and ORIENT-16 (N = 2,231) revealed that PD-1 blockade significantly improved OS in the CPS≥5 subgroup (HR = 0.69, 95% CI 0.60–0.79, P < 0.001), but not in the CPS<5 subgroup (HR = 0.96, 95% CI 0.82–1.13, P = 0.643). Interaction tests showed a significantly attenuated treatment effect on OS in the CPS<5 subgroup compared to the CPS≥5 subgroup (Pinteraction = 0.002). Similar findings were observed in the pooled analysis of PFS data (Pinteraction = 0.011).ConclusionThe addition of PD-1 inhibitors to first-line chemotherapy provides minimal benefit in patients with CPS<5. Therefore, PD-1 inhibitors should be individualized for this patient subset.